Synthesis of Glycouronamides by Transamidation Approach at Room Temperature - Kanaujiya V.K.; Tiwari V.; Pattanaik K.; Sabiah S.; Kandasamy J. (My University, 2025)
Synthesis of various glycouronamides via transamidation reaction is reported under mild reaction conditions. Transamidation of N-nitroso uronamides with primary and secondary amines was successfully achieved in the presence of triethyl amine. On the other hand, N-Boc uronamides underwent transamidation smoothly with various primary amines in the presence of DBU. These reactions provided the desired glycouroamides in good to excellent yields at room temperature. © 2022 Wiley-VCH GmbH.